Sulphur and Zn management in groundnut (Arachis hypogaea)-wheat (Triticum aestivum) cropping system: Direct effects on system productivity and residual effects on yield, energetics and Zn biofortification in wheat - NOMAN, HEBA M; RANA, D S; CHOUDHARY, ANIL K; RAJPOOT, S; PAUL, T (The Indian Journal of Agricultural Sciences, 2016)
A field experiment was conducted over two consecutive rainy (kharif) and winter (rabi) seasons of 2013–14 and 2014–15 at IARI, New Delhi; to evaluate the direct and residual effects of three sulphur (S) levels (0, 20 and 40 kg S/ ha), four zinc (Zn) levels (0, 2.5, 5 and 7.5 kg Zn/ha) and two zinc biofertilizer levels (control and zinc biofertilizer seed treatment) on the performance of groundnut (Arachis hypogaea L.)–wheat Triticum aestivum (L.) emend. Fiori & Paol. cropping system (GWCS). Results pertaining to direct effects on system productivity and residual effects on performance of wheat have been included in this paper. Across the seasons, residual effects of 40 kg S/ha and 5 and 7.5 kg Zn/ha were perceptible on the grain and straw yield, economics, energetics, and S and Zn uptake in wheat crop. Based on 2 years’ average, wheat grain yield increased by 4.9%, net profit by ` 4 200/ha and energy returns by 8.3×103 MJ due to residual effect of 40 kg S/ha over control. On an average, application of 5 and 7.5 kg Zn/ha to groundnut led to increased wheat grain yield by 4.1 and 4.5%, net profit by ` 3 300 and ` 4 000/ha, and energy returns by 6.1×103 and 7.8 ×103 MJ, respectively due to residual fertility. With successive increase in Zn–levels to groundnut, a significant Zn–enrichment of wheat grain and straw was also observed in the current study. However, no residual effect of Zn–solubilizer was noticed on wheat crop. On an average, application of 40 kg S/ha and 5 kg Zn/ha was found to enhance the GWCS system productivity by 16.8 and 12.2% over control, respectively; besides respective significant higher economic–efficiency of ` 299 and 287/ha/day. Perceptible variations were also noticed in the system productivity and economic–efficiency following Zn–solubilizer application over the control. Overall, it is concluded that application of S @ 40 kg/ha and Zn @ 5 kg/ha to groundnut had marked residual effect on wheat productivity, profitability, energy dynamics besides Zn biofortification in wheat. The direct application of S @ 40 kg/ ha and Zn @ 5 kg/ha also led to significant enhancement in groundnut pod yield, system productivity, system production- efficiency and system economic-efficiency as well, indicating that S @ 40 kg/ha and Zn @ 5 kg/ha are sufficient enough to meet the S and Zn requirement of GWCS.